2013
DOI: 10.1093/fampra/cms083
|View full text |Cite
|
Sign up to set email alerts
|

Developing a method to estimate practice denominators for a national Canadian electronic medical record database

Abstract: Background. Calculating disease prevalence requires both a numerator (number of persons with a disease) and a matching denominator (the 'population at risk' being studied). Determining primary care practice denominators is challenging.Objective. To develop and test a method to calculate primary care practice denominators. Methods.We compared a 'corrected yearly contact group', or practice population, with the number of patients enrolled with practices. The yearly contact group was the set of patients with a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…We first calculated the prevalence rates for COPD, classified by an appropriate age group and sex. We estimated the prevalence using the denominator described by Greiver and colleagues 19 because it approximates the general population while the 24-month contact group approximates those attending the practice. We then calculated age-and sex-standardized prevalence rates according to Canadian national age and sex distribution (census 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We first calculated the prevalence rates for COPD, classified by an appropriate age group and sex. We estimated the prevalence using the denominator described by Greiver and colleagues 19 because it approximates the general population while the 24-month contact group approximates those attending the practice. We then calculated age-and sex-standardized prevalence rates according to Canadian national age and sex distribution (census 2011).…”
Section: Discussionmentioning
confidence: 99%
“…No Canadá, 49% de médicos da atenção básica relataram o uso de um sistema RES em 2010 5 . Nos Estados Unidos 7 , na atenção ambulatorial, observou-se, em 2011, que 35% dos consultórios possuíam um RES básico.…”
Section: Discussionunclassified
“…In 2015, in Finland, 75% of PCUs had electronic records (World Health Organization, 2016). In Canada, 49% of primary care doctors reported using an EHR, in 2010 (Greiver et al, 2013). In 2011, in the United States (Black et al, 2011), usage of an HER was observed in 35% of outpatient care medical offices.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, a Canadian systematic review demonstrated that there was little evidence on specific benefits: EHRs were not precise enough to serve as base in clinical application; there was a lack of alignment between the EHR and the clinical work flow and the demonstrable value for the clinics was uncertain (Greiver et al, 2013). …”
mentioning
confidence: 99%